Vitamin E nanoemulsion activity on stored red blood cells. Issue 3 (23rd February 2017) - Silva, C. A. L.; Azevedo Filho, C. A.; Pereira, G.; Silva, D. C. N.; Castro, M. C. A. B.; Almeida, A. F.; Lucena, S. C. A.; Santos, B. S.; Barjas‐Castro, M. L.; Fontes, A.
SUMMARY: Background: Stored red blood cells (RBCs) undergo numerous changes that have been termed RBC storage lesion, which can be related to oxidative damage. Vitamin E is an important antioxidant, acting on cell lipids. Thus, this study aimed to investigate vitamin E activity on stored RBCs. Methods: We prepared a vitamin E nanoemulsion that was added to RBC units and stored at 4 °C. Controls, without vitamin E, were kept under the same conditions. Reactive oxygen species (ROS) production was monitored for up to 35 days of storage. RBC elasticity was also evaluated using an optical tweezer system. Results: Vitamin E‐treated samples presented a significant decrease in ROS production. Additionally, the elastic constant for vitamin E‐treated RBCs did not differ from the control. Conclusion: Vitamin E decreased the amount of ROS in stored RBCs. Because vitamin E acts on lipid oxidation, results suggest that protein oxidation should also be considered a key factor for erythrocyte elastic properties. Thus, further studies combining vitamin E with protein antioxidants deserve attention, aiming to better preserve overall stored RBC properties.